DISRUPTIONS, DISCONTINUITIES & DISPERSIONS: AN ETHNOGRAPHY OF DISJUNCTURES IN ACUTE ORTHOPAEDIC WARDS. (16th November 2018) - Penhale, B; Cross, J; Poland, F; Fox, C; Hammond, S; Backhouse, T
Abstract: Enhanced Recovery Pathways (ERPs) are based on the premise that evidence-based medicine can be brought to bear on a sequence of events to maximise throughput, productivity and quality in healthcare (in this case orthopaedic care in acute hospital settings). However, what is usual care is less well described in the literature and many health and care practitioners do not recognise this smooth and seamless construction of acute orthopaedic care. As part of a UK National Institute of Health Research Programme, in our study Peri-Operative Enhanced Recovery hip Fracture Care of patients with dementia (PERFECTED), we wanted to establish what happens in usual care on acute orthopaedic hospital wards, and how delirium and/or dementia impact on practice and to inform the development of an ERP for this population. Ethnographic observations of "public" care were undertaken in a number of different hospitals in the UK. The data from the observations richly identifies multiple types of disjunctures (disruptions and discontinuities and dispersions) that impact on patients and staff, and patients with delirium and/or dementia produce particular and specific impacts on care. Such practice dilemmas are known, but not well-captured in this setting, and knowledge gained may make a valuable contribution to understanding usual care. This session will enable participants to understand the value of ethnographic observations in health science research. It will also enable the Identification of disjunctures in acute settings and how these impact on usual care practices.